Implementing the RISE second victim support programme at the Johns Hopkins Hospital: a case study. Issue 9 (30th September 2016) - Edrees, Hanan; Connors, Cheryl; Paine, Lori; Norvell, Matt; Taylor, Henry; Wu, Albert W
Abstract : Background: Second victims are healthcare workers who experience emotional distress following patient adverse events. Studies indicate the need to develop organisational support programmes for these workers. The RISE (Resilience In Stressful Events) programme was developed at the Johns Hopkins Hospital to provide this support. Objective: To describe the development of RISE and evaluate its initial feasibility and subsequent implementation. Programme phases included (1) developing the RISE programme, (2) recruiting and training peer responders, (3) pilot launch in the Department of Paediatrics and (4) hospital-wide implementation. Methods: Mixed-methods study, including frequency counts of encounters, staff surveys and evaluations by RISE peer responders. Descriptive statistics were used to summarise demographic characteristics and proportions of responses to categorical, Likert and ordinal scales. Qualitative analysis and coding were used to analyse open-ended responses from questionnaires and focus groups. Results: A baseline staff survey found that most staff had experienced an unanticipated adverse event, and most would prefer peer support. A total of 119 calls, involving ∼500 individuals, were received in the first 52 months. The majority of calls were from nurses, and very few were related to medical errors (4%). Peer responders reported that the encounters were successful in 88% of cases and 83.3% reported meeting the caller's needs. Low awareness of the programme was a barrier to hospital-wide expansion. However, over the 4 years, the rate of calls increased from ∼1–4 calls per month. The programme evolved to accommodate requests for group support. Conclusions: Hospital staff identified the need for a multidisciplinary peer support programme for second victims. Peer responders reported success in responding to calls, the majority of which were for adverse events rather than for medical errors. The low initial volume of calls emphasises the importance of promoting awareness of the value of emotional support and the availability of the programme.